(untitled) (Global Journal of Computer Science and Technology, 2024)
The purpose of this study is to examine the present status of the literature with regard to the relationships among Industry 4 0 quality management and Total Quality Management TQM This article s goal was to identify the topics and concerns that should be brought up while discussing with regard to termed quality 4 0 A systematic review of the literature was used in this study For this review study around 15 papers from various sources were examined in total using predetermined selection and exclusion criteria The topics were divided into the following four categories creating value for the company using high-quality big data analysis as well as the use of artificial intelligence AI to develop a high-quality 4 0 culture and expertise for high-quality staff members co-creating value for customers and deploying cyber-physical platforms and enterprise resource planning ERP to assure quality and control This essay also attempted to investigate whether Quality 4 0 had a definition based on established practices